Podcast-Based Extensive Listening for Academic Purposes: A Case Study of Learner Autonomy and Comprehension - Rozak, Refi Ranto; Andini, Dafa Yanuar (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study investigated the use of podcasts as a means of Extensive Listening (EL) in an academic setting, with a focus on how it affects learner autonomy and listening comprehension. Although Extensive Reading (ER) is a well-known teaching method, its application to listening skills has not been widely explored, especially in academic environments. The research is based on a qualitative case study involving five students in their fourth semester at a university in Indonesia. Over a period of 12 weeks, these students participated in an EL program using English-language podcasts such as “TED Talks Daily,” “The Economist Editors’ Picks,” and “BBC Global News.” To gather data, the study used semi-structured interviews, listening journals, and pre- and post-program comprehension tests. The results show a clear positive link between regular participation in podcast-based EL and improvements in both learner autonomy shown through the students’ ability to choose their own materials, use listening strategies effectively, and stay motivated and their understanding of academic-style spoken content. The research concludes that using podcasts for EL is a powerful teaching method that helps learners take control of their language learning beyond the classroom, thus connecting structured education with real-life language usage.